Catastrophe and Environmental Restoration: Analyzing the Frames and Sources of Oyster Restoration News Stories - Hannah O Brown; Susan K Jacobson; Glenn Israel (Journal of Applied Communications, 2020)
Restoration of oyster habitats is a critical solution to halt the decline of one of the world’s most threatened resources. News coverage about environmental topics, like oyster restoration, is important to local communities that are directly impacted. However, little research has assessed how restoration topics are framed by journalists, nor how environmental disasters may affect framing of news stories for the public. This study employed a longitudinal framing analysis, using the quantity of coverage and social responsibility theories, to examine how coverage of the restoration of oyster ecosystems shifted before, during, and after the BP Deepwater Horizon oil spill. The frames and sources of 763 newspaper articles were assessed, including 18 local newspapers from five U.S. Gulf Coast states and three high-circulation national newspapers. Logistic regression analyses revealed that the occurrence of an environmental catastrophe shifted media focus from environmental frames before the spill to community and economic frames during and after the spill. Stories were dominated by environmental frames (49%) and primarily relied on quotes from resource managers (50%) over all other groups. Local resource users were quoted less than 5% of the time in local articles. Findings provide a foundation for natural resource managers and communication specialists to understand how information about natural resources changes during disasters and reveals the perspectives that are most and least commonly used to frame and define stories about coastal resources and important gaps in coverage.
Keywords: content analysis; ecosystem restoration; framing; newspaper; local source; risk communication